A Review on Methods of Enhancement And Denoising in Retinal Fundus Images - Bindhya, P.S; Chitra, R; Bibin Raj, V.S (International Journal of Computer Sciences and Engineering, 2020)
Diabetic Retinopathy (DR) is a disease caused by abnormalities in blood vessels in the eyes. DR can be detected in the early stages by the Detection of Micro Aneurysms in fundus retinal images. Retinal fundus pictures are commonly used for finding and analysis of DR disease that help ophthalmologists to complete the evaluation of retinal diseases. By reduction in noise level and by enhancing some features in the image pre-processing techniques are adopted. Restoration of images is done to happen by numerous pre-processing techniques. Here in this paper, the comparison of pre- processing in the retinal fundus image is done. For the precise visual view of DR-related highlights, the nature of fundus pictures should be enhanced to a satisfactory level. The difference is a more critical quality than a unique degree of splendor and goals. The main purpose of the pre-processing technique is to increase the diagnostic possibility in fundus images for visual assessment and also for computer-aided segmentation. This paper deals with the comparison of different retinal image denoising technique and their parameters such as MSE, PSNR, Correlation coefficient, RMS values, etc were reviewed and compared with different datasets for retinal images in connection with the identification of DR and Micro Aneurysms (MA).